Sulfur-tolerant hydrodechlorination catalyst with core-shell structure as well as preparation method and application of sulfur-tolerant hydrodechlorination catalyst

By adopting a sulfur-resistant hydrochlorination catalyst with a core-shell structure, the problem of inactivation of catalysts under sulfur-containing gas in the prior art is solved, and an efficient, stable and economical hydrochlorination effect is achieved.

CN119425712AActive Publication Date: 2025-02-14WUHAN HEGU ENVIRONMENTAL PROTECTION CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411781615.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-02-14
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The prior art lacks sulfur-resistant hydrochlorination catalysts suitable for sulfur-containing gas working conditions, resulting in rapid catalyst deactivation and equipment corrosion, affecting the safe operation and economic benefits of the enterprise.

Method used

A sulfur-resistant hydrochloric acid catalyst with a core-shell structure is used. The support of the catalyst is dodecanoic acid heptaalaluminate with a cage structure, the shell is titanium dioxide, and the active component contains Co and/or Ni and Mo and/ Or W, prepared by impregnation method.

Benefits of technology

It has achieved a high activity, good stability and moderate cost resistance to sulfur hydrochloric acid, which can effectively remove organic chlorine in sulfur-containing coal gas, extend the service life of the catalyst and reduce production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005172919550000011
    Figure BDA0005172919550000011
  • Figure BDA0005172919550000021
    Figure BDA0005172919550000021
  • Figure BDA0005172919550000231
    Figure BDA0005172919550000231
Patent Text Reader

Abstract

The invention provides a sulfur-tolerant hydrodechlorination catalyst with a core-shell structure as well as a preparation method and application of the sulfur-tolerant hydrodechlorination catalyst. The sulfur-tolerant hydrodechlorination catalyst disclosed by the invention is prepared by adopting an impregnation method, and a carrier takes C12A7 with a cage cavity structure as a core and TiO2 as a shell layer; the C12A7 of the cage cavity structure has abundant micro channels, so that Cl <-> and O2 <-> can enter conveniently, and meanwhile, a larger reactive surface is provided; tiO2 is a shell layer and forms a hydrodechlorination active center together with the active component; the three components have a synergistic effect, so that the hydrodechlorination activity can be improved, and the activity stability in a chlorine-containing atmosphere can be maintained; the sulfur-tolerant hydrodechlorination catalyst is sulfur-tolerant, is suitable for sulfur-containing atmosphere, and has no sulfur tolerance upper limit; the sulfur-tolerant hydrodechlorination catalyst disclosed by the invention is good in activity and stability, and is resistant to gases such as HCl which are toxic to the catalyst; the sulfur-tolerant hydrodechlorination catalyst with the core-shell structure is high in strength, and the crushing strength of particles is larger than or equal to 100 N / cm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrodechlorination catalysts, and in particular to a sulfur-resistant hydrodechlorination catalyst with a core-shell structure, and a preparation method and application thereof. Background Art

[0002] The chlorine content in my country's coal is between 0.01% and 0.20%, and most of it is below 0.05%. According to classification, most of it is low-chlorine coal and extra-low-chlorine coal. In the past 10 years, with the expansion of exploration scope, a large number of chlorine-containing coal seams have been discovered in Xinjiang, my country. For example, the chlorine content in some of the Sharhu coal can reach 1% (with reserves of 100 billion tons).

[0003] It is worth noting that although my country mainly produces low-chlorine coal and ultra-low-chlorine coal, chlorine may be enriched in a certain mine or coal seam in a specific mining area. There are still some coal mines with chlorine content exceeding 0.02% or 0.025%. For example, the chlorine content of coal in Hongyang, Liaoning, Handan, Hebei, Linfen, and Luliang, Shanxi is much higher than the national average chlorine content of coal mines. There are also reports that the average chlorine content in Huangling coal is as high as 637.67 mg / kg. Table 1 below shows the distribution of medium and high chlorine coal in my country.

[0004] Table 1 - Distribution of medium and high chlorine coal

[0005]

[0006]

[0007] In recent years, due to the gradual depletion of high-quality low-chlorine coal resources in the coal chemical industry, some enterprises (especially in Xinjiang) have partially or completely replaced low-chlorine coal with high-chlorine coal as gasification raw materials. High-chlorine coal is a typical low-quality coal. The chlorine in the coal can be released in the form of HCl, Cl2 and organic chlorine during the gasification process, which is carried to the back end with the raw gas, causing the catalyst in the back stage to deactivate quickly.

[0008] The inorganic chlorine (HCl, Cl2) can be effectively removed by water washing, dry dechlorination, etc., but there is currently no effective removal method for organic chlorine.

[0009] If a hydrodechlorination catalyst can be developed to convert the organic chlorine in coal gas into inorganic chlorine (HCl), and then effectively remove it through water washing, dry dechlorination, etc., it will be possible to avoid chlorine poisoning and deactivation of catalysts in the later stages and corrosion of equipment caused by chlorine, significantly improve the company's safe operation cycle, and enhance economic and social benefits.

[0010] At present, there are few reports on catalysts for hydrodechlorination of organic chlorine in coal gas at home and abroad. The prior art discloses a catalyst for selective hydrodechlorination of 1,2-dichloroethane, which uses titanium dioxide as a carrier and noble metals (Pd, Pt, Au or Ru) as active components. It is expensive and not resistant to sulfur. The prior art discloses a catalyst for catalytic hydrodechlorination, which uses activated carbon, silicon carbide or a mixture of the two as a carrier and noble metal Ru as an active component. It also has the problems of being expensive and not resistant to sulfur. The prior art discloses a method for catalytic hydrodechlorination, which uses nickel carbide nanocomposite materials as catalysts, has a complex preparation process, a high price, and is only suitable for liquid phase hydrodechlorination, and is not resistant to sulfur. The prior art discloses a catalytic hydrodechlorination catalyst, which uses aluminum oxide as a carrier, is suitable for hydrodechlorination of waste plastic cracking oil, and has a high reaction temperature (320°C). The prior art discloses a coking crude benzene hydrodechlorination catalyst, which uses Al2O3-SiO2 as a carrier and a mixture of nickel oxide, palladium oxide and molybdenum trioxide as an active component, is relatively expensive and is not resistant to sulfur. The prior art discloses a carbon-supported hydrodechlorination catalyst, which uses activated carbon as a carrier and precious metal Ru as an active component, has a complex preparation process, is relatively expensive, and is not resistant to sulfur.

[0011] It can be seen that the current research on sulfur-resistant hydrodechlorination catalysts suitable for sulfur-containing coal gas atmosphere is still insufficient. Most of the reported hydrodechlorination catalysts use precious metals as active components, which are expensive, not sulfur-resistant, and cannot be widely promoted and applied. Therefore, it is of great practical significance to develop a sulfur-resistant hydrodechlorination catalyst with high activity, moderate price, and suitable for the removal of organic chlorine under sulfur-containing coal gas working conditions. Summary of the invention

[0012] The purpose of the present invention is to provide a sulfur-resistant hydrodechlorination catalyst, which is suitable for removing organic chlorine in sulfur-containing coal gas and a preparation method thereof. The hydrodechlorination catalyst is a supported catalyst, the carrier has a cage structure of dodecalcium heptaaluminate (12CaO·7Al2O3, referred to as C12A7) as the core, titanium dioxide (TiO2) as the shell, and the active elements in the active component include Co and / or Ni and Mo and / or W. The sulfur-resistant hydrodechlorination catalyst of the present invention has the characteristics of high activity, good stability, moderate price, and is suitable for sulfur-containing coal gas working conditions, and can meet the requirements for the hydroremoval of organic chlorine in coal gas.

[0013] To achieve the above object, the present invention adopts the following technical solution:

[0014] In a first aspect, the present invention provides a sulfur-resistant hydrodechlorination catalyst having a core-shell structure, comprising a carrier and an active component supported on the carrier;

[0015] The carrier comprises a core layer and a shell layer coated outside the core layer;

[0016] Wherein, the core layer is dodecaluminate heptahedralite having a cage structure;

[0017] The shell layer is titanium dioxide;

[0018] The active elements in the active component include Co and / or Ni and Mo and / or W.

[0019] Preferably, the mass fraction of the shell layer in the carrier is 10 to 25%;

[0020] Among them, the sum of the masses of the Co element and the Ni element is 2-4% of the mass of the carrier, and the mass ratio of the Co element to the Ni element is (0-1.6):(0-1.6); the sum of the masses of the Mo element and the W element is 4-15% of the mass of the carrier, and the mass ratio of the Mo element to the W element is (0-5):(0-5).

[0021] In a second aspect, the present invention further provides a method for preparing the sulfur-resistant hydrodechlorination catalyst having a core-shell structure, comprising the following steps:

[0022] After mixing the Co source and / or the Ni source with the Mo source and / or the W source, adding ammonia water, and stirring to obtain an impregnation solution;

[0023] The carrier is added into the impregnation solution, stirred and then dried to obtain a sulfur-resistant hydrodechlorination catalyst with a core-shell structure.

[0024] Preferably, the carrier is added to the impregnation solution, stirred and then dried at 100 to 150° C. for 2 to 12 hours to obtain a sulfur-resistant hydrodechlorination catalyst having a core-shell structure.

[0025] Preferably, the Co source is cobalt nitrate;

[0026] The Ni source is nickel nitrate;

[0027] The Mo source is ammonium heptamolybdate;

[0028] The W source is ammonium tungstate.

[0029] Preferably, after mixing cobalt nitrate, nickel nitrate, ammonium heptamolybdate and ammonium tungstate, adding ammonia water, stirring to obtain an impregnation solution; adding the carrier to the impregnation solution, stirring to obtain an impregnated carrier;

[0030] The mass volume ratio of the cobalt nitrate, nickel nitrate, ammonium heptamolybdate, ammonium tungstate, carrier and ammonia water is (0-5) g: (0-5) g: (0-65) g: (0-61) g: (50-60) g: (20-25) mL;

[0031] The ratio of the sum of the mass of the cobalt nitrate and the nickel nitrate to the mass of the carrier is (3.5-6.5):(50-60);

[0032] The ratio of the sum of the mass of the ammonium heptamolybdate and the ammonium tungstate to the mass of the carrier is (30-65):(50-60);

[0033] The mass concentration of the ammonia water is 20-30%.

[0034] Preferably, the method for preparing the carrier comprises the following steps:

[0035] Preparation of calcium heptahedralite with cage structure;

[0036] After mixing calcium dodecaaluminate having a cage structure and a titanium source, water is added and kneaded to obtain a mixture;

[0037] The mixture is dried and then calcined to obtain a carrier.

[0038] Preferably, the titanium source is titanium sol;

[0039] In the step of mixing calcium dodecanedioaluminate with a cage structure and a titanium source, adding water, and kneading, the mass ratio of titanium dioxide to water in the calcium dodecanedioaluminate with a cage structure and the titanium sol is (75-90):(10-25):(40-60);

[0040] In the step of drying the mixture, the drying temperature is 100 to 150° C. and the drying time is 2 to 12 hours;

[0041] In the step of drying the mixture and then calcining it, the calcination temperature is 400 to 500° C. and the calcination time is 2 to 4 hours;

[0042] The preparation method of dodecacalcium heptaaluminate having a cage structure comprises:

[0043] Mixing an aluminum source and a calcium source to obtain a mixed powder;

[0044] Add nitric acid to water to obtain an acid solution;

[0045] Adding the mixed powder into the acid solution and mixing to obtain a wet powder;

[0046] The wet powder is dried at 100-150°C for 2-12 hours, and then calcined at 600-700°C for 2-4 hours to obtain dodecaluminate heptahedralite having a cage structure;

[0047] The aluminum source includes aluminum hydroxide and / or pseudo-boehmite;

[0048] The calcium source includes at least one of calcium carbonate, calcium hydroxide and calcium oxide;

[0049] The molar ratio of aluminum in the aluminum source to calcium in the calcium source is 7:6;

[0050] In the step of adding nitric acid to water, the nitric acid is a nitric acid solution with a mass fraction of 65-68%, and the mass ratio of the nitric acid solution to water is (3-5):(48-50);

[0051] In the steps of mixing an aluminum source and a calcium source to obtain a mixed powder and adding nitric acid into water, the molar ratio of aluminum in the aluminum source to water is 1:(2.67-2.78).

[0052] In a third aspect, the present invention also provides an application of the sulfur-resistant hydrodechlorination catalyst with a core-shell structure or the sulfur-resistant hydrodechlorination catalyst with a core-shell structure prepared by the preparation method in removing organic chlorine from sulfur-containing coal gas.

[0053] Preferably, in the application, the use conditions of the sulfur-resistant hydrodechlorination catalyst with a core-shell structure are: the use atmosphere is sulfur-containing coal gas, the reaction temperature is 180-320°C, the space velocity is 500-3000h -1 .

[0054] The sulfur-resistant hydrodechlorination catalyst with a core-shell structure and the preparation method thereof of the present invention have the following beneficial effects compared with the prior art:

[0055] The sulfur-resistant hydrodechlorination catalyst with a core-shell structure of the present invention is prepared by an impregnation method. The carrier has C12A7 with a cage structure as the core and TiO2 as the shell layer, which is a core-shell structure. The C12A7 with a cage structure has abundant micro-channels, which is convenient for Cl - , O 2- The invention discloses a sulfur-resistant hydrodechlorination catalyst having a core-shell structure and a sulfur-resistant hydrodechlorination catalyst having a core-shell structure. The sulfur-resistant hydrodechlorination catalyst has a core-shell structure and a sulfur-resistant surface. The core-shell structure provides a large reactive surface. The TiO2 is a shell layer and constitutes a hydrodechlorination active center together with the active component. The three have a synergistic effect, which can improve the hydrodechlorination activity and maintain the activity stability in a chlorine-containing atmosphere. The sulfur-resistant hydrodechlorination catalyst having a core-shell structure of the invention has high activity. Due to the unique core-shell structure, the three have a synergistic effect, which can improve the hydrodechlorination activity and maintain the activity stability in a chlorine-containing atmosphere. The sulfur-resistant hydrodechlorination catalyst having a core-shell structure of the invention is sulfur-resistant: suitable for sulfur-containing atmospheres, and has no upper limit on sulfur resistance. The sulfur-resistant hydrodechlorination catalyst having a core-shell structure of the invention has good activity stability: resistant to gases that are poisonous to the catalyst, such as HCl. The sulfur-resistant hydrodechlorination catalyst having a core-shell structure of the invention has high strength, and the particle crushing strength is ≥100N / cm. The sulfur-resistant hydrodechlorination catalyst having a core-shell structure of the invention does not use precious metals, and the raw materials are cheap and easy to obtain, and the cost is moderate. DETAILED DESCRIPTION

[0056] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0057] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any cited numbers (fractions or integers) within the indicated range.

[0058] The embodiment of the present application provides a sulfur-resistant hydrodechlorination catalyst having a core-shell structure, including a carrier and an active component supported on the carrier;

[0059] The carrier includes a core layer and a shell layer covering the core layer;

[0060] Among them, the core layer is calcium dodecaaluminate with a cage structure;

[0061] The shell is titanium dioxide;

[0062] The active elements in the active component include Co and / or Ni and Mo and / or W.

[0063] The sulfur-resistant hydrodechlorination catalyst with a core-shell structure of the present invention has calcium dodecaaluminate (C12A7) with a cage structure as the core and titanium dioxide (TiO2) as the shell layer. The C12A7 core is coated with TiO2, and the active elements in the active components include Co and / or Ni and Mo and / or W. The sulfur-resistant hydrodechlorination catalyst of the present invention is suitable for the hydrodechlorination of organic chlorine in sulfur-containing raw gas and coal gas, and has the remarkable advantages of unique structure, high activity, sulfur resistance, high strength, good activity stability, and moderate cost.

[0064] In some embodiments, the mass fraction of the shell layer in the carrier is 10-25%.

[0065] In some embodiments, the sum of the masses of Co and Ni elements is 2-4% of the mass of the carrier, and the mass ratio of Co and Ni elements is (0-1.6):(0-1.6); the sum of the masses of Mo and W elements is 4-15% of the mass of the carrier, and the mass ratio of Mo and W elements is (0-5):(0-5).

[0066] Preferably, the sum of the masses of the Co element and the Ni element is 2.36-3.96% of the mass of the carrier, and the mass ratio of the Co element to the Ni element is (0-1.57):(0-1.57); the sum of the masses of the Mo element and the W element is 6.67-10.00% of the mass of the carrier, and the mass ratio of the Mo element to the W element is (0-5.00):(0-4.26).

[0067] Based on the same inventive concept, the present invention also provides a method for preparing the above-mentioned sulfur-resistant hydrodechlorination catalyst with a core-shell structure, comprising the following steps:

[0068] S1, after mixing the Co source and / or the Ni source with the Mo source and / or the W source, adding ammonia water, and stirring to obtain an impregnation solution;

[0069] S2. Add the carrier into the impregnation solution, stir and dry to obtain a sulfur-resistant hydrodechlorination catalyst with a core-shell structure.

[0070] In some embodiments, the carrier is added to the impregnation solution, stirred and then dried at 100-150° C. for 2-12 hours to obtain a sulfur-resistant hydrodechlorination catalyst having a core-shell structure.

[0071] In some embodiments, the Co source is cobalt nitrate;

[0072] In some embodiments, the Ni source is nickel nitrate;

[0073] In some embodiments, the Mo source is ammonium heptamolybdate ((NH4)6Mo7O 24 4H2O);

[0074] In some embodiments, the W source is ammonium tungstate (hydrated ammonium tungstate, H 26 N6O 40 W 12 ).

[0075] In some embodiments, cobalt nitrate, nickel nitrate, ammonium heptamolybdate, and ammonium tungstate are mixed, and then ammonia water is added and stirred to obtain an impregnation solution; a carrier is added to the impregnation solution and stirred to obtain an impregnated carrier;

[0076] The mass volume ratio of cobalt nitrate, nickel nitrate, ammonium heptamolybdate, ammonium tungstate, carrier and ammonia water is (0-5) g: (0-5) g: (0-65) g: (0-61) g: (50-60) g: (20-25) mL;

[0077] The ratio of the sum of the mass of cobalt nitrate and nickel nitrate to the mass of the carrier is (3.5-6.5):(50-60);

[0078] The ratio of the sum of the mass of ammonium heptamolybdate and ammonium tungstate to the mass of the carrier is (30-65):(50-60);

[0079] The mass concentration of ammonia water is 20-30%.

[0080] Preferably, in some embodiments, the mass volume ratio of cobalt nitrate, nickel nitrate, ammonium heptamolybdate, ammonium tungstate, carrier, and ammonia water is (0.00-4.83) g: (0.00-4.89) g: (0.00-64.39) g: (0.00-60.14) g: (50-60) g: (20-25) mL;

[0081] The ratio of the sum of the mass of cobalt nitrate and nickel nitrate to the mass of the carrier is (3.65-6.07):(50-60);

[0082] The ratio of the sum of the masses of ammonium heptamolybdate and ammonium tungstate to the mass of the carrier is (30.05-64.39):(50-60).

[0083] In some embodiments, after cobalt nitrate and ammonium heptamolybdate are mixed, ammonia water is added and stirred to obtain an impregnation solution; a carrier is added to the impregnation solution and stirred to obtain an impregnated carrier; wherein the mass volume ratio of cobalt nitrate, ammonium heptamolybdate, carrier and ammonia water is (1.21-4.83) g:(25.76-64.39) g:(50-60) g:(20-25) mL; the mass concentration of ammonia water is 20-30%.

[0084] In some embodiments, cobalt nitrate, nickel nitrate, and ammonium heptamolybdate are mixed, ammonia water is added, and the mixture is stirred to obtain an impregnation solution; a carrier is added to the impregnation solution, stirred, and an impregnated carrier is obtained; wherein the mass volume ratio of cobalt nitrate, nickel nitrate, ammonium heptamolybdate, carrier, and ammonia water is (1.21-4.83) g:(1.22-4.89) g:(25.76-64.39) g:(50-60) g:(20-25) mL; and the mass concentration of ammonia water is 20-30%.

[0085] In some embodiments, cobalt nitrate, nickel nitrate, and ammonium tungstate are mixed, ammonia water is added, and the mixture is stirred to obtain an impregnation solution; a carrier is added to the impregnation solution, stirred to obtain an impregnated carrier; wherein the mass volume ratio of cobalt nitrate, nickel nitrate, ammonium tungstate, carrier, and ammonia water is (1.21-4.83) g:(1.22-4.89) g:(24.06-60.14) g:(50-60) g:(20-25) mL; the mass concentration of ammonia water is 20-30%.

[0086] In some embodiments, cobalt nitrate, nickel nitrate, ammonium heptamolybdate, and ammonium tungstate are mixed, ammonia water is added, and the mixture is stirred to obtain an impregnation solution; a carrier is added to the impregnation solution, stirred, and an impregnated carrier is obtained; wherein the mass volume ratio of cobalt nitrate, nickel nitrate, ammonium heptamolybdate, ammonium tungstate, carrier, and ammonia water is (1.21-4.83) g:(1.22-4.89) g:(25.76-64.39) g:(24.06-60.14) g:(50-60) g:(20-25) mL; the mass concentration of ammonia water is 20-30%.

[0087] In some embodiments, cobalt nitrate, nickel nitrate, and ammonium heptamolybdate are mixed, ammonia water is added, and the mixture is stirred to obtain an impregnation solution; a carrier is added to the impregnation solution, stirred, and an impregnated carrier is obtained; wherein the mass volume ratio of cobalt nitrate, nickel nitrate, ammonium heptamolybdate, carrier, and ammonia water is (1.21-4.83) g:(1.22-4.89) g:(25.76-64.39) g:(50-60) g:(20-25) mL; and the mass concentration of ammonia water is 20-30%.

[0088] In some embodiments, after cobalt nitrate and ammonium heptamolybdate are mixed, ammonia water is added and stirred to obtain an impregnation solution; a carrier is added to the impregnation solution and stirred to obtain an impregnated carrier; wherein the mass volume ratio of cobalt nitrate, ammonium heptamolybdate, carrier and ammonia water is (1.21-4.83) g:(25.76-64.39) g:(50-60) g:(20-25) mL; the mass concentration of ammonia water is 20-30%.

[0089] In some embodiments, nickel nitrate, ammonium heptamolybdate, and ammonium tungstate are mixed, ammonia water is added, and the mixture is stirred to obtain an impregnation solution; a carrier is added to the impregnation solution, stirred, and an impregnated carrier is obtained; wherein the mass volume ratio of nickel nitrate, ammonium heptamolybdate, carrier, and ammonia water is (1.22-4.89) g:(25.76-64.39) g:(50-60) g:(20-25) mL; and the mass concentration of ammonia water is 20-30%.

[0090] In some embodiments, cobalt nitrate, nickel nitrate, and ammonium heptamolybdate are mixed, ammonia water is added, and the mixture is stirred to obtain an impregnation solution; a carrier is added to the impregnation solution, stirred, and an impregnated carrier is obtained; wherein the mass volume ratio of cobalt nitrate, nickel nitrate, ammonium heptamolybdate, carrier, and ammonia water is (1.21-4.83) g:(1.22-4.89) g:(25.76-64.39) g:(50-60) g:(20-25) mL; and the mass concentration of ammonia water is 20-30%.

[0091] In some embodiments, the method for preparing the carrier comprises the following steps:

[0092] S11, preparing calcium heptahedralite having a cage structure;

[0093] S12, mixing calcium dodecaaluminate heptaaluminate having a cage structure and a titanium source, adding water, and kneading to obtain a mixture;

[0094] S13, drying the mixture and calcining it to obtain a carrier.

[0095] In some embodiments, the titanium source is titanium sol; titanium sol is prepared by dispersing nano-titanium dioxide powder (5-20 nm) in an aqueous medium to form a highly dispersed, homogenized and stabilized transparent liquid.

[0096] In some embodiments, after mixing calcium dodecanedioaluminate with a cage structure and a titanium source, water is added, and in the kneading step, the mass ratio of calcium dodecanedioaluminate with a cage structure and titanium dioxide in the titanium sol to water is (75-90): (10-25): (40-60);

[0097] In the step of drying the mixture, the drying temperature is 100 to 150° C. and the drying time is 2 to 12 hours;

[0098] In the step of calcining the mixture after drying, the calcination temperature is 400-500° C. and the calcination time is 2-4 hours.

[0099] In some embodiments, since the carrier of the present invention includes a core layer and a shell layer coated outside the core layer, the mass fraction of titanium dioxide (TiO2) in the shell layer is 10-25%, and the mass fraction of calcium dodecanoate heptaaluminate with a cage structure is 75-90%, that is, the mass ratio of titanium dioxide (TiO2) and calcium dodecanoate heptaaluminate with a cage structure is (10-25):(75-95). Since titanium dioxide (TiO2) is provided by titanium sol, the mass ratio of calcium dodecanoate heptaaluminate with a cage structure, titanium dioxide in the titanium sol, and water is (75-90):(10-25):(40-60).

[0100] In some embodiments, the preparation method of dodecaluminate heptaaluminate having a cage structure comprises:

[0101] S21, mixing an aluminum source and a calcium source to obtain a mixed powder;

[0102] S22, adding nitric acid to water to obtain an acid solution;

[0103] S23, adding the mixed powder to the acid solution, mixing, and obtaining a wet powder;

[0104] S24, drying the wet powder at 100-150° C. for 2-12 h, and then calcining at 600-700° C. for 2-4 h to obtain dodecaluminate heptahedralite having a cage structure;

[0105] The aluminum source includes aluminum hydroxide and / or pseudo-boehmite; specifically, pseudo-boehmite is also known as monohydrated aluminum oxide, pseudo-boehmite, and its English name is Pseudo Boehmite, AlOOH·nH2O, n=0.08-0.62;

[0106] The calcium source includes at least one of calcium carbonate, calcium hydroxide and calcium oxide;

[0107] The molar ratio of aluminum in the aluminum source to calcium in the calcium source is 7:6; specifically, since the chemical formula of dodecaluminate is 12CaO·7Al2O3, in which the molar ratio of aluminum to calcium is 7:6, the molar ratio of aluminum in the aluminum source to calcium in the calcium source is 7:6;

[0108] In the step of adding nitric acid to water, the nitric acid is a nitric acid solution with a mass fraction of 65-68%, and the mass ratio of the nitric acid solution to water is (3-5):(48-50);

[0109] In the steps of mixing an aluminum source and a calcium source to obtain a mixed powder and adding nitric acid into water, the molar ratio of aluminum in the aluminum source to water is 1:(2.67-2.78).

[0110] Specifically, in some embodiments, calcium dodecaaluminate heptaaluminate having a cage structure and a titanium source are mixed, water is added, and the mixture is kneaded to obtain a mixture; the mixture is then placed in a mold and formed into a strip shape, and the strip-shaped mixture is dried and calcined to obtain a carrier.

[0111] The sulfur-resistant hydrodechlorination catalyst with a core-shell structure of the present invention is prepared by an impregnation method. The carrier is a core of C12A7 with a cage structure and a shell of TiO2. The C12A7 with a cage structure has abundant microchannels, which facilitates Cl - , O 2-The invention discloses a sulfur-resistant hydrodechlorination catalyst having a core-shell structure, wherein the sulfur-resistant hydrodechlorination catalyst has ...

[0112] Based on the same inventive concept, the present invention also provides an application of the above-mentioned sulfur-resistant hydrodechlorination catalyst with a core-shell structure or the sulfur-resistant hydrodechlorination catalyst with a core-shell structure prepared by the above-mentioned preparation method in removing organic chlorine from sulfur-containing coal gas.

[0113] In some embodiments, the use conditions of the sulfur-resistant hydrodechlorination catalyst with a core-shell structure are: the use atmosphere is sulfur-containing coal gas, the reaction temperature is 180-320°C, the space velocity is 500-3000h -1 .

[0114] The following further illustrates the sulfur-resistant hydrodechlorination catalyst with a core-shell structure of the present application and its preparation method and application with specific examples. This section further illustrates the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0115] Example 1

[0116] The present application provides a method for preparing a sulfur-resistant hydrodechlorination catalyst having a core-shell structure, comprising the following steps:

[0117] S1, 0.85714 mol of calcium hydroxide powder and 1 mol of pseudo-boehmite powder are mixed to obtain a mixed powder (the molar ratio of aluminum to calcium in the mixed powder is 7:6);

[0118] S2, add 5g of nitric acid (aqueous solution of nitric acid) with a mass concentration of 68% to 50g (i.e. 2.78mol) of water, and fully dissolve to obtain a clear and transparent solution, which is the acid solution;

[0119] S3, adding the mixed powder in S1 to the acid solution in S2, mixing, and obtaining a wet powder;

[0120] S4, drying the wet powder in S3 at 100°C for 12 hours, and then calcining at 700°C for 2 hours to obtain dodecaluminate heptahedralite having a cage structure;

[0121] S5, after mixing 75g of calcium heptaaluminate with a cage structure in S4 and titanium sol (the mass of nano titanium dioxide powder in the titanium sol is 25g, and the average particle size is 15nm) (the mass ratio of calcium heptaaluminate and titanium dioxide is calculated to be 75:25), 50g of water is added, and kneading is performed to obtain a mixture;

[0122] S6, placing the mixture in S5 in a mold (the mold is a hollow cylindrical shape with an inner diameter of 4 mm) and molding it into a strip-shaped mixture;

[0123] S7, drying the strip-shaped mixture in S6 at 150°C for 2 hours, and then calcining at 500°C for 2 hours to obtain a carrier;

[0124] S8, after mixing 4.83g of cobalt nitrate and 42.93g of ammonium heptamolybdate, add 20mL of 25% ammonia water, stir and dissolve to obtain an impregnation solution;

[0125] S9. Add 50 g of the carrier in step S7 to the impregnation solution in step S8, stir, place for 15 hours, and then dry at 100° C. for 12 hours to obtain a sulfur-resistant hydrodechlorination catalyst with a core-shell structure.

[0126] Example 2

[0127] The present application provides a method for preparing a sulfur-resistant hydrodechlorination catalyst having a core-shell structure, comprising the following steps:

[0128] S1, 0.85714 mol of calcium hydroxide powder and 1 mol of pseudo-boehmite powder are mixed to obtain a mixed powder (the molar ratio of aluminum to calcium in the mixed powder is 7:6);

[0129] S2, add 5g of nitric acid (aqueous solution of nitric acid) with a mass concentration of 68% to 50g (i.e. 2.78mol) of water, and fully dissolve to obtain a clear and transparent solution, which is the acid solution;

[0130] S3, adding the mixed powder in S1 to the acid solution in S2, mixing, and obtaining a wet powder;

[0131] S4, drying the wet powder in S3 at 120°C for 4 hours, and then calcining at 650°C for 3 hours to obtain dodecaluminate heptahedralite having a cage structure;

[0132] S5, after mixing 85g of calcium heptaaluminate with a cage structure and titanium sol (the mass of nano-titanium dioxide powder in the titanium sol is 15g, and the average particle size is 15nm) (the mass ratio of calcium heptaaluminate and titanium dioxide is calculated to be 85:15), 50g of water is added, and kneading is performed to obtain a mixture;

[0133] S6, placing the mixture in S5 in a mold (the mold is a hollow cylindrical shape with an inner diameter of 4 mm) and molding it into a strip-shaped mixture;

[0134] S7, drying the strip-shaped mixture in S6 at 120°C for 4 hours, and then calcining at 450°C for 3 hours to obtain a carrier;

[0135] S8, after mixing 2.41g of cobalt nitrate, 2.45g of nickel nitrate, and 42.93g of ammonium heptamolybdate, adding 20mL of 25% ammonia water, stirring and dissolving to obtain an impregnation solution;

[0136] S9. Add 50 g of the carrier in step S7 to the impregnation solution in step S8, stir, place for 15 hours, and then dry at 120° C. for 4 hours to obtain a sulfur-resistant hydrodechlorination catalyst with a core-shell structure.

[0137] Example 3

[0138] The present application provides a method for preparing a sulfur-resistant hydrodechlorination catalyst having a core-shell structure, comprising the following steps:

[0139] S1, 0.85714 mol of calcium hydroxide powder and 1 mol of pseudo-boehmite powder are mixed to obtain a mixed powder (the molar ratio of aluminum to calcium in the mixed powder is 7:6);

[0140] S2, add 5g of nitric acid (aqueous solution of nitric acid) with a mass concentration of 68% to 50g (i.e. 2.78mol) of water, and fully dissolve to obtain a clear and transparent solution, which is the acid solution;

[0141] S3, adding the mixed powder in S1 to the acid solution in S2, mixing, and obtaining a wet powder;

[0142] S4, drying the wet powder in S3 at 150°C for 2 hours, and then calcining at 600°C for 4 hours to obtain dodecaluminate heptahedralite having a cage structure;

[0143] S5, 90g of calcium heptaaluminate with a cage structure in S4 and titanium sol (the mass of nano-titanium dioxide powder in the titanium sol is 10g, and the average particle size is 15nm) are mixed (the mass ratio of calcium heptaaluminate to titanium dioxide is calculated to be 90:10), 50g of water is added, and kneading is performed to obtain a mixture;

[0144] S6, placing the mixture in S5 in a mold (the mold is a hollow cylindrical shape with an inner diameter of 4 mm) and molding it into a strip-shaped mixture;

[0145] S7, drying the strip-shaped mixture in S6 at 100°C for 12 hours, and then calcining at 400°C for 4 hours to obtain a carrier;

[0146] S8, after mixing 2.41g of cobalt nitrate, 2.45g of nickel nitrate, and 60.14g of ammonium tungstate, add 20mL of 25% ammonia water, stir and dissolve to obtain an impregnation solution;

[0147] S9. Add 50 g of the carrier in step S7 to the impregnation solution in step S8, stir, place for 15 hours, and then dry at 150° C. for 2 hours to obtain a sulfur-resistant hydrodechlorination catalyst with a core-shell structure.

[0148] Example 4

[0149] The present application provides a method for preparing a sulfur-resistant hydrodechlorination catalyst having a core-shell structure, comprising the following steps:

[0150] S1, 0.85714 mol of calcium hydroxide powder and 1 mol of pseudo-boehmite powder are mixed to obtain a mixed powder (the molar ratio of aluminum to calcium in the mixed powder is 7:6);

[0151] S2, add 5g of nitric acid (aqueous solution of nitric acid) with a mass concentration of 68% to 50g (i.e. 2.78mol) of water, and fully dissolve to obtain a clear and transparent solution, which is the acid solution;

[0152] S3, adding the mixed powder in S1 to the acid solution in S2, mixing, and obtaining a wet powder;

[0153] S4, drying the wet powder in S3 at 150°C for 2 hours, and then calcining at 600°C for 4 hours to obtain dodecaluminate heptahedralite having a cage structure;

[0154] S5, 90g of calcium heptaaluminate with a cage structure in S4 and titanium sol (the mass of nano-titanium dioxide powder in the titanium sol is 10g, and the average particle size is 15nm) are mixed (the mass ratio of calcium heptaaluminate to titanium dioxide is calculated to be 90:10), 50g of water is added, and kneading is performed to obtain a mixture;

[0155] S6, placing the mixture in S5 in a mold (the mold is a hollow cylindrical shape with an inner diameter of 4 mm) and molding it into a strip-shaped mixture;

[0156] S7, drying the strip-shaped mixture in S6 at 100°C for 12 hours, and then calcining at 400°C for 4 hours to obtain a carrier;

[0157] S8, after mixing 2.41g of cobalt nitrate, 2.45g of nickel nitrate, 25.76g of ammonium heptamolybdate, and 24.06g of ammonium tungstate, 20mL of 25% ammonia water was added, and the mixture was stirred and dissolved to obtain an impregnation solution;

[0158] S9. Add 50 g of the carrier in step S7 to the impregnation solution in step S8, stir, place for 15 hours, and then dry at 150° C. for 2 hours to obtain a sulfur-resistant hydrodechlorination catalyst with a core-shell structure.

[0159] Example 5

[0160] The present application provides a method for preparing a sulfur-resistant hydrodechlorination catalyst having a core-shell structure, comprising the following steps:

[0161] S1, 0.85714 mol of calcium hydroxide powder and 1 mol of pseudo-boehmite powder are mixed to obtain a mixed powder (the molar ratio of aluminum to calcium in the mixed powder is 7:6);

[0162] S2, add 5g of nitric acid (aqueous solution of nitric acid) with a mass concentration of 68% to 50g (i.e. 2.78mol) of water, and fully dissolve to obtain a clear and transparent solution, which is the acid solution;

[0163] S3, adding the mixed powder in S1 to the acid solution in S2, mixing, and obtaining a wet powder;

[0164] S4, drying the wet powder in S3 at 120°C for 4 hours, and then calcining at 650°C for 3 hours to obtain dodecaluminate heptahedralite having a cage structure;

[0165] S5, after mixing 85g of calcium heptaaluminate with a cage structure in S4 and titanium sol (the mass of nano-titanium dioxide powder in the titanium sol is 20g, and the average particle size is 15nm) (the mass ratio of calcium heptaaluminate and titanium dioxide using this ratio is calculated to be 85:20), 50g of water is added, and kneading is performed to obtain a mixture;

[0166] S6, placing the mixture in S5 in a mold (the mold is a hollow cylindrical shape with an inner diameter of 4 mm) and molding it into a strip-shaped mixture;

[0167] S7, drying the strip-shaped mixture in S6 at 120°C for 4 hours, and then calcining at 450°C for 3 hours to obtain a carrier;

[0168] S8, after mixing 2.41g of cobalt nitrate, 2.45g of nickel nitrate, and 42.93g of ammonium heptamolybdate, adding 20mL of 25% ammonia water, stirring and dissolving to obtain an impregnation solution;

[0169] S9. Add 50 g of the carrier in step S7 to the impregnation solution in step S8, stir, place for 15 hours, and then dry at 120° C. for 4 hours to obtain a sulfur-resistant hydrodechlorination catalyst with a core-shell structure.

[0170] Example 6

[0171] The present application provides a method for preparing a sulfur-resistant hydrodechlorination catalyst having a core-shell structure, comprising the following steps:

[0172] S1, 0.85714 mol of calcium hydroxide powder and 1 mol of pseudo-boehmite powder are mixed to obtain a mixed powder (the molar ratio of aluminum to calcium in the mixed powder is 7:6);

[0173] S2, add 5g of nitric acid (aqueous solution of nitric acid) with a mass concentration of 68% to 50g (i.e. 2.78mol) of water, and fully dissolve to obtain a clear and transparent solution, which is the acid solution;

[0174] S3, adding the mixed powder in S1 to the acid solution in S2, mixing, and obtaining a wet powder;

[0175] S4, drying the wet powder in S3 at 120°C for 4 hours, and then calcining at 650°C for 3 hours to obtain dodecaluminate heptahedralite having a cage structure;

[0176] S5, after mixing 85g of calcium heptaaluminate with a cage structure in S4 and titanium sol (the mass of nano-titanium dioxide powder in the titanium sol is 20g, and the average particle size is 15nm) (the mass ratio of calcium heptaaluminate and titanium dioxide using this ratio is calculated to be 85:20), 50g of water is added, and kneading is performed to obtain a mixture;

[0177] S6, placing the mixture in S5 in a mold (the mold is a hollow cylindrical shape with an inner diameter of 4 mm) and molding it into a strip-shaped mixture;

[0178] S7, drying the strip-shaped mixture in S6 at 120°C for 4 hours, and then calcining at 450°C for 3 hours to obtain a carrier;

[0179] S8, after mixing 4.83g of cobalt nitrate and 42.93g of ammonium heptamolybdate, add 20mL of 25% ammonia water, stir and dissolve to obtain an impregnation solution;

[0180] S9. Add 50 g of the carrier in step S7 to the impregnation solution in step S8, stir, place for 15 hours, and then dry at 120° C. for 4 hours to obtain a sulfur-resistant hydrodechlorination catalyst with a core-shell structure.

[0181] Example 7

[0182] The present application provides a method for preparing a sulfur-resistant hydrodechlorination catalyst having a core-shell structure, comprising the following steps:

[0183] S1, 0.85714 mol of calcium hydroxide powder and 1 mol of pseudo-boehmite powder are mixed to obtain a mixed powder (the molar ratio of aluminum to calcium in the mixed powder is 7:6);

[0184] S2, add 5g of nitric acid (aqueous solution of nitric acid) with a mass concentration of 68% to 50g (i.e. 2.78mol) of water, and fully dissolve to obtain a clear and transparent solution, which is the acid solution;

[0185] S3, adding the mixed powder in S1 to the acid solution in S2, mixing, and obtaining a wet powder;

[0186] S4, drying the wet powder in S3 at 120°C for 4 hours, and then calcining at 650°C for 3 hours to obtain dodecaluminate heptahedralite having a cage structure;

[0187] S5, after mixing 85g of calcium heptaaluminate with a cage structure in S4 and titanium sol (the mass of nano-titanium dioxide powder in the titanium sol is 20g, and the average particle size is 15nm) (the mass ratio of calcium heptaaluminate and titanium dioxide using this ratio is calculated to be 85:20), 50g of water is added, and kneading is performed to obtain a mixture;

[0188] S6, placing the mixture in S5 in a mold (the mold is a hollow cylindrical shape with an inner diameter of 4 mm) and molding it into a strip-shaped mixture;

[0189] S7, drying the strip-shaped mixture in S6 at 120°C for 4 hours, and then calcining at 450°C for 3 hours to obtain a carrier;

[0190] S8, after mixing 4.89g of nickel nitrate and 42.93g of ammonium heptamolybdate, add 20mL of 25% ammonia water, stir and dissolve to obtain an impregnation solution;

[0191] S9. Add 50 g of the carrier in step S7 to the impregnation solution in step S8, stir, place for 15 hours, and then dry at 120° C. for 4 hours to obtain a sulfur-resistant hydrodechlorination catalyst with a core-shell structure.

[0192] Example 8

[0193] The present application provides a method for preparing a sulfur-resistant hydrodechlorination catalyst having a core-shell structure, comprising the following steps:

[0194] S1, 0.85714 mol of calcium hydroxide powder and 1 mol of pseudo-boehmite powder are mixed to obtain a mixed powder (the molar ratio of aluminum to calcium in the mixed powder is 7:6);

[0195] S2, add 5g of nitric acid (aqueous solution of nitric acid) with a mass concentration of 68% to 50g (i.e. 2.78mol) of water, and fully dissolve to obtain a clear and transparent solution, which is the acid solution;

[0196] S3, adding the mixed powder in S1 to the acid solution in S2, mixing, and obtaining a wet powder;

[0197] S4, drying the wet powder in S3 at 120°C for 4 hours, and then calcining at 650°C for 3 hours to obtain dodecaluminate heptahedralite having a cage structure;

[0198] S5, after mixing 85g of calcium heptaaluminate with a cage structure in S4 and titanium sol (the mass of nano-titanium dioxide powder in the titanium sol is 20g, and the average particle size is 15nm) (the mass ratio of calcium heptaaluminate and titanium dioxide using this ratio is calculated to be 85:20), 50g of water is added, and kneading is performed to obtain a mixture;

[0199] S6, placing the mixture in S5 in a mold (the mold is a hollow cylindrical shape with an inner diameter of 4 mm) and molding it into a strip-shaped mixture;

[0200] S7, drying the strip-shaped mixture in S6 at 120°C for 4 hours, and then calcining at 450°C for 3 hours to obtain a carrier;

[0201] S8, after mixing 2.41g of cobalt nitrate, 1.22g of nickel nitrate, and 64.39g of ammonium heptamolybdate, adding 22mL of 25% ammonia water, stirring and dissolving to obtain an impregnation solution;

[0202] S9. Add 50 g of the carrier in step S7 to the impregnation solution in step S8, stir, place for 15 hours, and then dry at 120° C. for 4 hours to obtain a sulfur-resistant hydrodechlorination catalyst with a core-shell structure.

[0203] Example 9

[0204] The present application provides a method for preparing a sulfur-resistant hydrodechlorination catalyst having a core-shell structure, comprising the following steps:

[0205] S1, 0.85714 mol of calcium hydroxide powder and 1 mol of pseudo-boehmite powder are mixed to obtain a mixed powder (the molar ratio of aluminum to calcium in the mixed powder is 7:6);

[0206] S2, add 5g of nitric acid (aqueous solution of nitric acid) with a mass concentration of 68% to 50g (i.e. 2.78mol) of water, and fully dissolve to obtain a clear and transparent solution, which is the acid solution;

[0207] S3, adding the mixed powder in S1 to the acid solution in S2, mixing, and obtaining a wet powder;

[0208] S4, drying the wet powder in S3 at 120°C for 4 hours, and then calcining at 650°C for 3 hours to obtain dodecaluminate heptahedralite having a cage structure;

[0209] S5, after mixing 85g of calcium heptaaluminate with a cage structure in S4 and titanium sol (the mass of nano-titanium dioxide powder in the titanium sol is 20g, and the average particle size is 15nm) (the mass ratio of calcium heptaaluminate and titanium dioxide using this ratio is calculated to be 85:20), 50g of water is added, and kneading is performed to obtain a mixture;

[0210] S6, placing the mixture in S5 in a mold (the mold is a hollow cylindrical shape with an inner diameter of 4 mm) and molding it into a strip-shaped mixture;

[0211] S7, drying the strip-shaped mixture in S6 at 120°C for 4 hours, and then calcining at 450°C for 3 hours to obtain a carrier;

[0212] S8, after mixing 3.62g of cobalt nitrate, 2.45g of nickel nitrate, and 30.05g of ammonium heptamolybdate, adding 20mL of 25% ammonia water, stirring and dissolving to obtain an impregnation solution;

[0213] S9. Add 50 g of the carrier in step S7 to the impregnation solution in step S8, stir, place for 15 hours, and then dry at 120° C. for 4 hours to obtain a sulfur-resistant hydrodechlorination catalyst with a core-shell structure.

[0214] Example 10

[0215] The present application provides a method for preparing a sulfur-resistant hydrodechlorination catalyst having a core-shell structure, comprising the following steps:

[0216] S1, 0.85714 mol of calcium hydroxide powder and 1 mol of pseudo-boehmite powder are mixed to obtain a mixed powder (the molar ratio of aluminum to calcium in the mixed powder is 7:6);

[0217] S2, add 5g of nitric acid (aqueous solution of nitric acid) with a mass concentration of 68% to 50g (i.e. 2.78mol) of water, and fully dissolve to obtain a clear and transparent solution, which is the acid solution;

[0218] S3, adding the mixed powder in S1 to the acid solution in S2, mixing, and obtaining a wet powder;

[0219] S4, drying the wet powder in S3 at 120°C for 4 hours, and then calcining at 650°C for 3 hours to obtain dodecaluminate heptahedralite having a cage structure;

[0220] S5, after mixing 85g of calcium heptaaluminate with a cage structure in S4 and titanium sol (the mass of nano-titanium dioxide powder in the titanium sol is 20g, and the average particle size is 15nm) (the mass ratio of calcium heptaaluminate and titanium dioxide using this ratio is calculated to be 85:20), 50g of water is added, and kneading is performed to obtain a mixture;

[0221] S6, placing the mixture in S5 in a mold (the mold is a hollow cylindrical shape with an inner diameter of 4 mm) and molding it into a strip-shaped mixture;

[0222] S7, drying the strip-shaped mixture in S6 at 120°C for 4 hours, and then calcining at 450°C for 3 hours to obtain a carrier;

[0223] S8, after mixing 1.21g of cobalt nitrate, 2.45g of nickel nitrate, and 64.39g of ammonium heptamolybdate, 22mL of 25% ammonia water was added, and the mixture was stirred and dissolved to obtain an impregnation solution;

[0224] S9. Add 50 g of the carrier in step S7 to the impregnation solution in step S8, stir, place for 15 hours, and then dry at 120° C. for 4 hours to obtain a sulfur-resistant hydrodechlorination catalyst with a core-shell structure.

[0225] Comparative Example 1

[0226] This comparative example discloses a hydrodechlorination catalyst and a preparation method thereof, comprising the following steps:

[0227] S1, weighing 118g of pseudo-boehmite, mixing with 2g of sesbania powder and 100g of 5wt% dilute nitric acid, kneading into a paste, then extruding into strips, and drying at 120°C for 8h and calcining at 530°C for 7h to obtain a catalyst carrier;

[0228] S2, weighing 43g of ammonium heptamolybdate and 21g of nickel nitrate, adding them into 150mL of deionized water to prepare an active metal impregnation solution, then weighing 100g of the above-mentioned carrier and saturating it in the impregnation solution for 10h, and finally drying at 135°C for 5h and calcining at 520°C for 6h to obtain a catalyst semi-finished product containing Ni and Mo active metals;

[0229] S3. Weigh 6.6 g of ammonium dihydrogen phosphate and add it to 90 mL of deionized water to prepare an auxiliary agent impregnation solution. Then weigh 100 g of the above-mentioned catalyst semi-finished product and saturate impregnate it in the impregnation solution for 6 hours. Finally, dry it at 150° C. for 7 hours and calcine it at 540° C. for 6.5 hours to obtain a hydrodechlorination catalyst containing 4.8 wt% of nickel oxide, 25.0 wt% of molybdenum oxide and 3.0 wt% of phosphorus oxide.

[0230] Performance Testing

[0231] The activity, strength and other properties of the sulfur-resistant hydrodechlorination catalysts with a core-shell structure prepared in Examples 1 to 10 and the hydrodechlorination catalyst prepared in Comparative Example 1 were tested.

[0232] The catalyst strength test is measured on an intelligent strength meter using a lateral pressure strength meter.

[0233] The hydrodechlorination performance test was carried out in a quartz glass reaction tube with a diameter of 28 mm. The sulfur-resistant hydrodechlorination catalysts with a core-shell structure prepared in Examples 1 to 10 and the hydrodechlorination catalyst prepared in Comparative Example 1 were cut into particles with a height-to-diameter ratio of approximately 1 (the specific catalysts were cut into cylindrical shapes with a diameter of 4 mm and a height of 4 mm), respectively, and placed in a quartz glass reaction tube. Gas was introduced, and the gas was simulated coal gas, with the main composition (v / v): 18% CO, 20% H2, 9% CO2, CH2Cl2 100 ppm, H2S 500 ppm, and the remainder was N2 (i.e., the volume concentration of CO in the simulated coal gas was 18%, the volume concentration of H2 was 20%, the volume concentration of CO2 was 9%, the volume concentration of CH2Cl2 was 0.01%, the volume concentration of H2S was 0.05%, and the rest was N2); the volume space velocity was 2000 h -1 , reaction temperature is 200℃, reaction pressure is 0.8Mpa, activity is expressed by CH2Cl2 conversion rate (hydrodechlorination reaction formula: CH2Cl2+2H2=CH4+2HCl). Pre-sulfurization is performed according to HG / T2780-2016 before evaluation. Test results are shown in Table 2.

[0234] Table 2 - Hydrodechlorination activity test results of different catalysts

[0235]

[0236] As can be seen from Table 2, the sulfur-resistant hydrodechlorination catalysts in Examples 1 to 10 have significantly higher CH2Cl2 conversion rates than Comparative Example 1, and all show very high activity (>95%), with the highest activity reaching 99.8% (Example 5). As the amount of titanium dioxide added increases, the compressive strength gradually increases, showing a significant correlation. As the amount of active component loading increases, the compressive strength also shows a gradual increasing trend. It is well known that improving the compressive strength is beneficial to reducing the resistance of the catalyst bed in industrial production, reducing power consumption in industrial production, and extending the service life of the catalyst. The above data show that the catalyst and preparation method thereof proposed in the present invention have significant advantages.

[0237] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A sulfur-resistant hydrodechlorination catalyst having a core-shell structure, characterized in that: It includes a carrier and an active component loaded on the carrier; The carrier comprises a core layer and a shell layer coated outside the core layer; Wherein, the core layer is dodecaluminate heptahedralite having a cage structure; The shell layer is titanium dioxide; The active elements in the active component include Co and / or Ni and Mo and / or W.

2. The sulfur-resistant hydrodechlorination catalyst with a core-shell structure according to claim 1, characterized in that: The mass fraction of the shell layer in the carrier is 10 to 25%; Among them, the sum of the masses of the Co element and the Ni element is 2-4% of the mass of the carrier, and the mass ratio of the Co element to the Ni element is (0-1.6):(0-1.6); the sum of the masses of the Mo element and the W element is 4-15% of the mass of the carrier, and the mass ratio of the Mo element to the W element is (0-5):(0-5).

3. A method for preparing a sulfur-resistant hydrodechlorination catalyst having a core-shell structure as claimed in any one of claims 1 to 2, characterized in that: The following steps are involved: After mixing the Co source and / or the Ni source with the Mo source and / or the W source, adding ammonia water, and stirring to obtain an impregnation solution; The carrier is added into the impregnation solution, stirred and then dried to obtain a sulfur-resistant hydrodechlorination catalyst with a core-shell structure.

4. The method for preparing the sulfur-resistant hydrodechlorination catalyst having a core-shell structure according to claim 3, characterized in that: The carrier is added into the impregnation solution, and after stirring, it is dried at 100-150° C. for 2-12 hours to obtain a sulfur-resistant hydrodechlorination catalyst with a core-shell structure.

5. The method for preparing the sulfur-resistant hydrodechlorination catalyst having a core-shell structure according to claim 3, characterized in that: The Co source is cobalt nitrate; The Ni source is nickel nitrate; The Mo source is ammonium heptamolybdate; The W source is ammonium tungstate.

6. The method for preparing the sulfur-resistant hydrodechlorination catalyst having a core-shell structure according to claim 5, characterized in that: After mixing cobalt nitrate, nickel nitrate, ammonium heptamolybdate and ammonium tungstate, adding ammonia water, stirring to obtain an impregnation solution; adding a carrier to the impregnation solution, stirring to obtain an impregnated carrier; The mass volume ratio of the cobalt nitrate, nickel nitrate, ammonium heptamolybdate, ammonium tungstate, carrier and ammonia water is (0-5) g: (0-5) g: (0-65) g: (0-61) g: (50-60) g: (20-25) mL; The ratio of the sum of the mass of the cobalt nitrate and the nickel nitrate to the mass of the carrier is (3.5-6.5):(50-60); The ratio of the sum of the mass of the ammonium heptamolybdate and the ammonium tungstate to the mass of the carrier is (30-65):(50-60); The mass concentration of the ammonia water is 20-30%.

7. The method for preparing the sulfur-resistant hydrodechlorination catalyst having a core-shell structure according to claim 3, characterized in that: The preparation method of the carrier comprises the following steps: Preparation of calcium heptahedralite with cage structure; After mixing calcium dodecaaluminate having a cage structure and a titanium source, water is added and kneaded to obtain a mixture; The mixture is dried and then calcined to obtain a carrier.

8. The method for preparing the sulfur-resistant hydrodechlorination catalyst having a core-shell structure according to claim 6, characterized in that: The titanium source is titanium sol; In the step of mixing calcium dodecanedioaluminate with a cage structure and a titanium source, adding water, and kneading, the mass ratio of titanium dioxide to water in the calcium dodecanedioaluminate with a cage structure and the titanium sol is (75-90):(10-25):(40-60); In the step of drying the mixture, the drying temperature is 100 to 150° C. and the drying time is 2 to 12 hours; In the step of drying the mixture and then calcining it, the calcination temperature is 400 to 500° C. and the calcination time is 2 to 4 hours; The preparation method of dodecacalcium heptaaluminate having a cage structure comprises: Mixing an aluminum source and a calcium source to obtain a mixed powder; Add nitric acid to water to obtain an acid solution; Adding the mixed powder into the acid solution and mixing to obtain a wet powder; The wet powder is dried at 100-150°C for 2-12 hours, and then calcined at 600-700°C for 2-4 hours to obtain dodecaluminate heptahedralite having a cage structure; The aluminum source includes aluminum hydroxide and / or pseudo-boehmite; The calcium source includes at least one of calcium carbonate, calcium hydroxide and calcium oxide; The molar ratio of aluminum in the aluminum source to calcium in the calcium source is 7:6; In the step of adding nitric acid to water, the nitric acid is a nitric acid solution with a mass fraction of 65-68%, and the mass ratio of the nitric acid solution to water is (3-5):(48-50); In the steps of mixing an aluminum source and a calcium source to obtain a mixed powder and adding nitric acid into water, the molar ratio of aluminum in the aluminum source to water is 1:(2.67-2.78).

9. Use of the sulfur-resistant hydrodechlorination catalyst with a core-shell structure as claimed in any one of claims 1 to 2 or the sulfur-resistant hydrodechlorination catalyst with a core-shell structure prepared by the preparation method as claimed in any one of claims 3 to 8 in removing organic chlorine from sulfur-containing coal gas.

10. The use according to claim 9, wherein the use conditions of the sulfur-resistant hydrodechlorination catalyst with a core-shell structure are: the use atmosphere is sulfur-containing coal gas, the reaction temperature is 180-320°C, and the space velocity is 500-3000h -1 .

Citation Information

Patent Citations

  • Chlorine-containing organic waste gas catalytic combustion catalyst and preparation method thereof

    CN110787797A

  • Dechlorinating agent as well as preparation method and application thereof

    CN115634569A

  • Ammonia synthesis catalyst and ammonia producing method

    JP2017148810A

  • Catalytic hydrogenation process

    US5149893A

  • Catalysts

    US5220110A